Synthesis of Novel Bis-Coumarin Derivatives as Potential Acetylcholinesterase Inhibitors: An In Vitro, Molecular Docking, and Molecular Dynamics Simulations Study - Zhila Zare-Akbari; Ladan Edjali; Moosa Eshaghi (Mazandaran University of Medical Sciences, 2022)
Background: Alzheimer disease is a progressive and irreversible disease that finally leads to death. It destroys cognitive skills and memory, and eventually, the patient cannot do the simplest things. Objectives: Cholinesterases (ChEs) which has the capability to control cholinergic transmission would result in elevating acetylcholine levels in the brain, by inhibiting CHEs. Coumarins have been shown to exhibit the inhibitory effect of cholinesterase, where the aromatic component results in designing novel candidates that can inhibit Ab accumulation. Methods: The condensation of aryl aldehydes and 4-hydroxycoumarin. Besides, we applied ZnO nanoparticles as an effective heterogeneous catalyst in [bmim]BF4. To determine the inhibitory activity, we used a substrate, i.e., acetylthiocholine iodide, to assay the tested compounds. Moreover, we applied Ellman's assay. Results: The present research is an in vitro work. It explores the possible binding mode of these compounds inside the Acetylcholinesterase (AChE) enzyme. Moreover, regarding the synthesized coumarin derivatives, we also performed docking and Molecular Dynamics (MD) simulation studies. The results indicate a satisfactory inhibitory activity for the assayed compounds against AChE with IC50 values from 0.100 to 0.02 µM. In this sense, the stability of protein-ligand complexes and the interaction of the compounds can be understood by performing a molecular docking with molecular dynamics simulation of 5000 ps in the solvent system for AChE.  Conclusion: Finally, it is worth mentioning that we also tested coumarin derivatives (L14 and L15), leading to potent and effective AChE inhibitors.